BLEEDING FROM UPPER GASTROINTESTINAL TRACT AT AL- DIWANIYAH-IRAQ; A RETROSPECTIVE STUDY OF ENDOSCOPIC RECORDS. - Abdlmaged, Mohammed Abdlmohsin; Muslim, OsamahTahir; Nejm, Abbas Hamza (International Journal of Psychosocial Rehabilitation, 2020)
Bleeding from upper gastrointestinal tract is a world wide serious and life-threatening medical emergency that needs hospitalization with optimal treatment. It is common in males than females. The prevalence rate rises with increasing age. Esophagogastroduodenoscopy is a valuable device in determining cause, location ofbleeding from upper gastrointestinal tract as well as establishing endoscopic treatment. Objectives: The purpose of this study is to evaluate the endoscopic findings for those patients presented with bleeding from upper gastrointestinal tract and the distribution of these findings in relation to patient’s age and sex. Patients and methods: The study done at AL-Diwaniyahgastroenterology and hepatology center in Iraq in a periodbetween November 2015 and November 2017. The endoscopic records of (225) patientspresented with bleeding from upper gastrointestinal tract and underwent esophagogastroduodenoscopy, are analyzed and evaluated in correlationwith age and sex of patients. Results: (225) patients presented with bleeding from upper gastrointestinal tractand underwent esophagogastroduodenoscopy.(141males, 62.67%) and (84 females, 37.33%) in a ratio of (1.7:1), The mean age of presentation is(43.71years). Patient’s age range is (9-85 years). Hematemesis is the commonest mode of presentation in patients with bleeding from upper gastrointestinal tract(51.50%) and the most common finding on endoscopy are peptic ulcers (duodenal and gastric ulcers),(41.33%); (81 patients) have duodenal ulcer (36 %) and (12 patients) have gastric ulcer (5.33%). The otherfindings consist of gastric erosion (13.33%), esophageal variceswith or without gastric varices (10.67%), gastrodoudenitis (7.55%), gastritis (7.55%), CA stomach (3.55%) and gastroesophageal reflux disease (GERD) (2.67%). Esophagitis and vascular ectasia: each one cause show (2.22%),Mallory-Wiess tears (1.78%) and Dieulafoy, s lesionshow (0.9%). No cause identified by endoscopy is recorded in (6.23%). Conclusions: Peptic ulcers (duodenal ulcer more than gastric ulcer) arethe commonest endoscopic finding in those patients presented withbleeding from upper gastrointestinal tract and the males areaffected more than females.